Master and commander : the far side of the world - Goldwyn, Samuel, Jr., 1926-2015.; Henderson, Duncan; Weir, Peter, 1944-; Crowe, Russell, 1964-; Bettany, Paul, 1971-; D'Arcy, James; Woodall, Edward; O'Brian, Patrick, 1914-2000.; Twentieth Century-Fox Film Corporation; Miramax Films; Universal Pictures (Firm); Samuel Goldwyn Films (Firm); et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2003)
During the Napoleonic Wars, a British frigate, the HMS Surprise, and the larger French warship, Acheron, stalk each other off of the coast of South America. Lucky Jack, as he is referred to by his crew, is well regarded by his men, who trust him implicitly, even after the first devastating battle and an apparent personal vendetta against the French captain. The ship's surgeon balances the violence of his chosen life with the quiet demeanor of the scientist. He is the captain's friend and confidant, the two frequently playing violin and cello duets together.
Rated PG-13.
Title from disc.
Originally released as a motion picture in 2003 ; 2004 DVD release.
Based upon the novels by Patrick O'Brian.
5.1 Dolby (English) ; Dolby surround (Spanish) ; 5.1 Dolby surround (French).
Director of photography, Russell Boyd ; editor, Lee Smith ; original music, Iva Davies, Christopher Gordon, Richard Tognetti ; costume designer, Kacy Treadway, Wendy Stites ; production designer, William Sandell ; visual effects supervisor, Mitchell S. Drain.
Keywords: 1800-1815; Napoleonic Wars, 1800-1815 -- Drama; Navies -- Officers -- Drama; Feature films; Films for the hearing impaired; Drama